2023
DOI: 10.1152/physrev.00028.2021
|View full text |Cite
|
Sign up to set email alerts
|

Physiological roles of hydrogen sulfide in mammalian cells, tissues, and organs

Abstract: H2S belongs to the class of molecules known as gasotransmitters, which also includes nitric oxide (NO) and carbon monoxide (CO). Three enzymes are recognized as endogenous sources of H2S in various cells and tissues: cystathionine g-lyase (CSE), cystathionine β-synthase (CBS) and 3-mercaptopyruvate sulfurtransferase (3-MST). The current article reviews the regulation of these enzymes as well as the pathways of their enzymatic and non-enzymatic degradation and elimination. The multiple interactions of H2S with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
142
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 181 publications
(183 citation statements)
references
References 2,195 publications
3
142
0
2
Order By: Relevance
“…Taken together, in control cells H 2 S does not appear to play a large role in modulating mitochondrial function and proliferation, while in DS cells, the elevated H 2 S levels exerts inhibitory effects on mitochondrial function and cell proliferation. Indeed, H 2 S has a well-documented ability to inhibit mitochondrial Complex IV, leading to the suppression of cellular bioenergetics and cell viability; an action which has been well characterized by earlier environmental toxicological and biochemical studies [ 3 , 4 , 17 , 18 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Taken together, in control cells H 2 S does not appear to play a large role in modulating mitochondrial function and proliferation, while in DS cells, the elevated H 2 S levels exerts inhibitory effects on mitochondrial function and cell proliferation. Indeed, H 2 S has a well-documented ability to inhibit mitochondrial Complex IV, leading to the suppression of cellular bioenergetics and cell viability; an action which has been well characterized by earlier environmental toxicological and biochemical studies [ 3 , 4 , 17 , 18 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…However, the proteomic analysis did not reveal very significant differences in the expression of enzymes involved in the regulation of central carbon metabolism, yielding the overall conclusion is that the changes that we observe in terms of bioenergetics and fluxomics are not principally driven by changes in rate limiting enzyme levels, but, rather, by functional biochemical effects, which may be driven by mechanisms that regulate the catalytic activity, rather than the expression level of these proteins. Among many mediators, H 2 S can induce such effects, for instance through persulfidation of protein cysteines or through its actions on metal-containing active centers [ 4 ]. For instance, in cancer cells, H 2 S has been shown to drive SQR-dependent respiration causing a reversal of the TCA cycle, glutamine deprivation, increased glycolysis and lipogenesis – effects that are not ultimately linked to altered expression of SQR protein [ 42 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, H 2 S has also been found to alleviate oxidative stress and maintain redox homeostasis through its ability to upregulate the cellular antioxidant mechanisms in an Nrf2-dependent manner [ 54 ]. Increasing evidence suggests that modifying thiol groups of cysteine residues in target proteins via S-sulfhydration or persulfidation is an important post-translational modification by H 2 S that is responsible for the biological functions of this gaseous signaling molecule [ 55 , 56 ]. Some animal studies have demonstrated that H 2 S donors that release H 2 S can S-sulfhydrate Keap1 at cysteine-151, leading to Nrf2 dissociation from Keap1 and promoting Nrf2 nuclear translocation, ultimately inducing the expression of downstream protective genes [ 57 , 58 , 59 ].…”
Section: Antioxidant Activities: a Conventional Anti-aging Paradigm O...mentioning
confidence: 99%